Living with cancer experiences and coping strategies of breast cancer survivors in Iloilo - Villaluz, Sarah Agatha A.
This study focused on the experiences and various coping strategies that breast cancer survivors have employed in order to come to terms with their disease. The most common challenge for breast cancer survivors is acceptance of their disease, but once that hurdle is overcome, it is much easier to combat the disease. Overall, breast cancer has made women more aware of their health, reminded them of their mortality and the impermanence of things.